Enhancing the innovation capability in dairy farms through knowledge sharing - Muhammad Imdad Ullah; Kamal Bin Ab Hamid; Arfan Shahzad; Zeeshan Mahmood (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2017)
The purpose of this paper is to develop and evaluate the framework for enhancing the innovation capability in dairy farms through knowledge sharing. It was hypothesized that trust, motivation, training and development are positively associated with knowledge sharing and that knowledge sharing between employees and managers impact positively on the innovation capability of the firms. The questionnaire based survey was used to collect the date from 254 randomly selected dairy farms that are located in the Punjab region of Pakistan. For data analysis SMART PLS-SEM 3.00 was used. The results of this paper confirmed all hypothesized relationships except the impact of trust on knowledge sharing which may be due to the unique contextual setting of Pakistan. This paper concludes that employees feel delighted in sharing knowledge for enhancing the innovation capability when they feel motivated and are provided with proper trainings.
Keywords: 330; dairy farms; innovation capability; motivation; Punjab; Pakistan; trust; training and development